Orbital Adnexal Malignant Tumours: A Report of Two Cases - Deepali Singh; Doyel Halder; Ankita Pranab Mandal; Mamata Guha Mallick Sinha (National Journal of Laboratory Medicine, 2023)
Sebaceous carcinoma of the eyelid is a very rare malignant tumour, accounting for 1-1.5% of total eyelid malignancies. It typically arises from the meibomian glands, making it more common in the upper eyelids. It predominantly affects individuals in their sixth to eighth decade, with a higher incidence in females. Histologically, the tumour cells are arranged in well-defined lobules with circumscribed borders. These cells exhibit pleomorphism, eccentric hyperchromatic nuclei, inconspicuous nucleoli, and multivacuolated cytoplasm. The clinical course of sebaceous carcinoma is aggressive, often characterised by recurrences and metastasis to regional lymph nodes. Unfortunately, it is not commonly considered in the differential diagnosis of eyelid tumours, leading to delayed treatment. Thus, it is crucial to raise awareness about this uncommon neoplasm occurring at unusual sites in order to improve patient survival. In the present case report, the authors present two cases: a 54-year-old male patient with intraocular sebaceous carcinoma, which recurred, and an 83-year-old male patient with extraocular sebaceous carcinoma. In both the cases, imaging and other investigations were performed, followed by excision of the mass and confirmation of the diagnosis through histopathological reporting. Subsequent follow-up was conducted for both cases and the postoperative recovery was uneventful.